(untitled) (Dhaka University Journal of Biological Sciences, 2021)
The lower Atrai basin, the study area, lies in the Agroecological Zone-5 (AEZ-5) of Bangladesh. This study reveals the clay mineral composition of top soils of seven different soil series viz. Binsara, Taras, Jaonia, Hasnabad, Laskara, Manda and Mainam developed in the basin. X-ray diffraction (XRD) technique was employed to identify and quantify the minerals. Results show that mica (41 to 59%) was the most dominant mineral among all soils except Laskara. In Laskara soils, the interstratified mica-vermiculite-smectite (41%) was the predominant mineral. Next to mica, kaolinite (10 to 12%) was found to be present in the Binsara, Taras 1, Jaonia, and Taras 2 soils. Chlorite (7 to 17%) was identified in all the soils and was found to be the second dominant mineral in the Manda and Mainam soils. In contrast, the interstratified mica-vermiculitesmectite (33%) was found to be the second dominant mineral in the Hasnabad soils. Small amounts of vermiculite mineral (1 to 13%) were identified in almost all the soils except Binsara. All the soils have interstratified mica-chlorite minerals (2 to 7%). A tiny amount of smectite (1%) was identified in Taras 1 soil. As far as the clay mineralogical composition is concerned, most studied soils were found at the initial stage of weathering, indicating the high potential to sustain low input subsistence agriculture. Dhaka Univ. J. Biol. Sci. 30(2): 293-306, 2021 (July)